Jurisdictional approaches to sustainable resource use - Essen, Marius; Lambin, Eric F (Frontiers in ecology and the environment, 2021)
Tropical forests are under increasing pressure, but conservation interventions have had only limited success in mitigating deforestation and ecosystem degradation. Over the past decade, however, jurisdictional approaches to sustainable resource use have attracted increasing attention as a potential alternative to traditional conservation strategies. These approaches operate within formal administrative boundaries and seek to establish policies and practices that apply to all stakeholders. We compiled a global database of conservation initiatives and developed a definition and typology for jurisdictional approaches; of the 80 initiatives included in our database, 25 met this definition. We categorized these jurisdictional approaches according to two criteria: the focus of the intervention and the degree of government involvement. These jurisdictions encompassed approximately 40% of global tropical forests, with most experiencing higher‐than‐average deforestation rates. Although jurisdictional approaches harbor the potential to overcome the limitations of previous approaches, numerous challenges for implementation and operation remain. In addition, because most jurisdictional initiatives currently in operation are still early in their lifecycles, the long‐term effectiveness of this strategy has yet to be proven.